Advancing Diversity, Equity, and Inclusion in School Psychology: Be the Change. Issue 1 (15th February 2021) - Jimerson, Shane R.; Arora, Prerna; Blake, Jamilia J.; Canivez, Gary L.; Espelage, Dorothy L.; Gonzalez, Jorge E.; Graves, Scott L.; Huang, Francis L.; January, Stacy-Ann A.; Renshaw, Tyler L.; Song, Samuel Y.; Sullivan, Amanda L.; et al.
Abstract: Individually and collectively, it is now more important than ever that we engage in intentional and sustained action to advocate for and advance diversity, equity, and inclusion (DEI) in the field of school psychology. To create positive change and the momentum to sustain it, it is essential that school psychology colleagues, organizations, and entities—including journals—identify how each can contribute to advancing DEI efforts. Herein, the School Psychology Review leadership team offers a brief summary of several of our intentional efforts, to date, to advocate for and advance DEI in school psychology scholarship. These actions toward accountability include (a) establishing individual and collective commitments to advocating for and advancing DEI as the foundation of our scholarship; (b) diversifying the journal leadership; (c) diversifying the editorial advisory board; (d) preparing future diverse journal leadership through mentored editorial fellowship programs, especially focused on early research career individuals; (e) mentoring future colleagues by establishing a student editorial board with members from diverse backgrounds; (f) focusing on special topics relevant to diverse and minoritized children, youth, families, and school communities; (g) making available professional-development opportunities and resources; and (h) establishing a journal action plan focused on advancing DEI. All colleagues, organizations, and entities are invited to individually and collectively join us to Be the Change in advancing and sustaining DEI efforts in school psychology scholarship. IMPACT STATEMENT The School Psychology Review leadership team outlines actions to advocate for and advance diversity, equity, and inclusivity in school psychology scholarship. Actions and accountability discussed include: establishing individual and collective commitments; diversifying the journal leadership, as well as the editorial advisory board; establishing journal infrastructures to support further development and contributions of diverse students and early career colleagues; and establishing a journal action plan focused on advancing diversity, equity, and inclusion.